Designing P92 grade martensitic steel header pipes against creep–fatigue interaction loading condition: Damage micromechanisms. (5th December 2015) - Gopinath K,; Gupta, R.K.; Sahu, J.K.; Ray, P.K.; Ghosh, R.N.
Abstract: The boiler tubes and pipes in the present day coal fired power plants are designed against damage arising from the interaction of creep and fatigue. The present investigation reports the microstructural evolution in P92 grade martensitic steel during pure fatigue and hold time fatigue tests conducted at 600 °C. Fatigue life significantly dropped for hold time fatigue tests in comparison with pure fatigue tests. The drop in fatigue life was more for hold time fatigue tests conducted with compressive hold. Grain boundary oxidation and cracking was identified as the major cause for the decrease in fatigue life under compressive hold. Annihilation of dislocations and pinning of dislocations by MX precipitates were observed to be the microstructural changes during cyclic deformation. Graphical abstract: Highlights: Fatigue life significantly dropped during RF tests with compressive hold. Grain boundary oxidation/cracking was the main cause of decrease in fatigue life. Annihilation/pinning of dislocations by MX were the major substructural changes.